2008
DOI: 10.1021/jp804643c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Dipole Moment on the Redox-Induced Reorganization of α-Helical Peptide Self-Assembled Monolayers: An Electrochemical SPR Investigation

Abstract: Self-assembled monolayers (SAMs) of ferrocene-labeled α-helical peptides were prepared on gold surfaces and studied using electrochemical surface plasmon resonance (EC-SPR). The leucine-rich peptides were synthesized with a cysteine sulfhydryl group either at the C-or N-terminus, enabling their immobilization onto gold surfaces with control of the direction of the molecular dipole moment. Two electroactive SAMs were studied, one in which all of the peptide dipole moments are oriented in the same direction (SAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…This effect was ascribed to the attractive interchain interactions taking place between opposing helical macrodipoles in the bicomponent SAM. Kraatz and co-workers 70,71 also demonstrated that, even if peptide SAMs are dynamical systems, in the antiparallel dipole arrangement, the peptide chains experience a more restricted motion due to stronger intermolecular interactions. The assembly of supramolecular structures on the basis of the intermolecular interaction of molecular electric dipoles (molecular dipole engineering) has been therefore proposed as a promising tool for the design of nanomaterials and nanodevices.…”
Section: Soft Engineering Of Bicomponent Peptide Samsmentioning
confidence: 99%
“…This effect was ascribed to the attractive interchain interactions taking place between opposing helical macrodipoles in the bicomponent SAM. Kraatz and co-workers 70,71 also demonstrated that, even if peptide SAMs are dynamical systems, in the antiparallel dipole arrangement, the peptide chains experience a more restricted motion due to stronger intermolecular interactions. The assembly of supramolecular structures on the basis of the intermolecular interaction of molecular electric dipoles (molecular dipole engineering) has been therefore proposed as a promising tool for the design of nanomaterials and nanodevices.…”
Section: Soft Engineering Of Bicomponent Peptide Samsmentioning
confidence: 99%
“…This free carboxyl group is important for further coupling of an antibody, enabling the use of the peptide in molecular recognition applications such as by forming functionalized surface for biosensor applications when coupled to a metallic plate. The amino acid Isoleucine was chosen due to the hydrophobicity and volume of side chain, resulting in the presence of hydrophobic and intramolecular hydrogen bonding in the peptide molecules . The volume of the branched increased in the order alkanethiol < Ala < Ile.…”
Section: Resultsmentioning
confidence: 99%
“…[53][54][55] This is in accordance with experimental observations where the dipole moment can facilitate charge transfer if the charge propagation (in the form of hole transfer) follows the same direction as the dipole moment in helical peptides. 12,56 Since each of the forward superexchange charge transfer steps has a negative energy difference (DE Aib1,Aib6 ), it is therefore energetically more favorable for the transference of cationic (+1) charge from the states Aib1 to Aib6, than the backward superexchange charge transfer step (Aib6 / Aib1), which is energetically unfavorable according to the Arrhenius' equation. Notably, there is a positive energy gap (DE Aib1,Aib4 ) in 3 (approx.…”
Section: Electron Transfer Mechanismsmentioning
confidence: 99%